ANÁLISE DO USO DE VIDROS SIMPLES E INSULADOS EM JANELAS DE UMA EDIFICAÇÃO CONDICIONADA ARTIFICIALMENTE - Kamimura, Artur; Motta, Leila Aparecida de Castro (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The design of a building, especially in what concerns the architectural project, should be attentive to questions such as thermal comfort and energy consumption. Both for design and for execution, it is important to make an analysis in order to optimize the performance of the building and measure the financial gains possible with such design. This work aims to propose constructive solutions that allow an increase of the energy efficiency of the building together with the gain of thermal comfort. In this way, possible constructive variations are considered, which allows, through successive improvements in the exterior envelope and glazed spans, to reduce the final consumption of energy and thus optimize to the maximum the energy performance of the building. Finally, it is possible to conclude that the reduction of energy consumption with window change is significant, so that the exchange of windows is a viable alternative for buildings of this size.